UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TURI (Sesbania grandiflora L) TERHADAP PERTUMBUHAN Stapylococcus aureus DENGAN METODE CAKRAM - Jamila Fachrunisa Kabakoran; Amelia Niwele; Mustamar Yuyun (Lembaga Pengembangan Kinerja Dosen, 2022)
Turi leaves (Sesbania grandiflora L) have potential as antimicrobials against pathogens because contains secondary metabolites of tannins and saponins which work as antimicrobials.The purpose of this study was to determine the content of secondary metabolites from ethanol extract Turi leaves (Sesbania grandiflora L) and antibacterial activity of the ethanol extract of turi leaves (Sesbania grandiflora L) on the growth of Staphylococcus aureus bacteria. The method used in this research is Disc Diffusion with concentration variants of 25%, 50%, 75% and 100% and amoxicillin as positive control. The results of this study indicate that the ethanol extract of Turi leaves (Sesbania grandiflora L) contains tannin and saponin secondary metabolites works as a compound that inhibits the growth of Staphylococcus aureus bacteria, test results antibacterial activity at concentrations of 25% and 50% had the diameter of the inhibition zone formed of 20mm and 24mm, whereas at a concentration of 100% it is very strong and effective in inhibits the growth of Staphylococcus aureus bacteria due to the diameter of the inhibition zone formed of 33mm, whereas in the positive control amoxicillin had a very strong inhibition zone in inhibiting the growth of Staphylococcus aureus bacteria with an inhibition zone diameter of 30mm.